Bioactive compounds and extraction techniques - Alam, Md. Ariful; Sarker, Md. Zaidul Islam; Ghafoor, Kashif; Happy, Rukshana Akter; Ferdosh, Sahena (John Wiley & Sons, 2017)
Bioactive compounds can be categorised according to their pharmacological activity, but the way of classification is complicated because of the dissimilarities between chemically interrelated compounds and the similarities between different molecules. Selection of an appropriate extraction process is a pivotal step because it influences the characterisation of bioactive compounds. Analysis of thermodynamic process and experimental design can help ensure maximal reproducibility of the extraction process. Different extraction technologies have been studied as non-conventional methods to enhance the extraction output and the release of bioactive compounds from natural sources, such as supercritical fluid extraction (SFE), subcritical water extraction (SWE), and microwave-assisted extraction (MAE). Enzymatic treatment of plant materials prior to extraction is a way to enhance mass transfer and the discharge of bounded secondary metabolites. Enzymes are perfect catalysing agents, which ease the breakdown and hydrolysis of complex materials on cell walls and membranes during extraction, causing alteration or synthesis of bioactive constituents of plant origin.